Using time series in the prediction of Iraqi GDPfor the period (2019-2028) - Hadi, Sawsan Qassim (International Journal of Psychosocial Rehabilitation, 2020)
Gross domestic product (GDP) is defined as the value of output of goods and services achieved within a year and is an important measure of the size of the economy’s output. This study aims to predict the Iraqi GDP for the following period, where the annual time series data for the period from 1970 to 2018 were obtained from the National Accounts Directorate / Central Statistical Organization / Ministry of Planning. Using the GRETL, the appropriate statistical model for the Iraqi GDP is an ARIMA (0.2,1). According to the data of this study, the Iraqi GDP is predicted for the next ten years (2019-2028) based on the ARIMR model (0.2). 1) The results showed an increase in the Iraqi GDP.